Peran Atribut Produk dalam Keputusan Pembelian Terkait Strategi Pemasaran Soyjoy di Area Bogor - - Rheinnadia; Abdul Kohar Irwanto; Mukhamad Najib (Institut Pertanian Bogor, 2016)
Food business competition in Indonesia is very diverse, because this promising industry is populated only by several large and small companies. Among the wide range of products produced by the company, there are not many food products making health as daily consumption product. Soyjoy is the first healthy product bar in Indonesia. Soyjoy sales in the Bogor area actually showed growth each year. These conditions encourage PT Amerta Indah Otsuka as Soyjoy producer to innovate and develop products with different attributes of the product in order to attract consumers to make purchases. This research is aimed to describe the Soyjoy consumer characteristics and sales trends in the area of Bogor, the effect of quality, brand image, pricing, and packaging (jointly or partial) on Soyjoy consumer buying interest and which attributes is the most dominant influence on buying interest Soyjoy in Bogor area analyzed by Structural Equation Modeling (SEM). The study showed that the quality, brand image and price positive and significant impact on consumer buying interest, and consumer buying interest and a significant positive influence on purchasing decisions. This research may provide an answer to the problem that quality is the consumer top priority in determining the choice between healthy snacks in the market. To improve purchasing decisions, companies need to increase buying interest in advance through product quality, brand image and price.